Phenotypic and functional activation of alveolar macrophages, T lymphocytes and NK cells in patients with systemic sclerosis and primary Sjögren's syndrome. Issue 9 (September 1994) - Gudbjörnsson, B; Hällgren, R; Nettelbladt, O; Gustafsson, R; Mattsson, A; af Geijerstam, E; Tötterman, T H
Abstract : OBJECTIVES--Attempts to differentiate between the pathogenesis of the severe pulmonary manifestations observed in systemic sclerosis (SSc) and the mild form in primary Sjögren's syndrome (pSS) were performed by studying cell populations recovered during bronchoalveolar lavage (BAL). METHODS AND RESULTS--Two-colour flow cytometric analysis of BAL fluid lymphocytes showed a similar degree of phenotypic activation (DR+) of CD4+ and CD8+ T lymphocyte subsets and CD16+ NK cells in patients with SSc (n = 13) and pSS (n = 11) groups and healthy controls (n = 11). Alveolar macrophages expressed the CD14 antigen at significantly increased densities in patients with SSc. Alveolar macrophage activation in SSc was also suggested by increased IL-6 concentrations in neat BAL fluid and increases in macrophage production of TNF alpha and EGF in vitro. SSc patients also had increased proportions of neutrophils and eosinophils in BAL fluid. No correlations were found between any cellular subsets or cytokine levels in BAL fluid and lung status at the time of lavage in SSc or pSS patients or the subsequent course of the pulmonary function in SSc patients. CONCLUSION--It is concluded that the phenotypical activation of alveolar helper/inducer (DR+CD4+) and suppressor/cytotoxic (DR+CD8+) T lymphocytes and NK (DR+CD16+) cells is not a prerequisite for the development of lung fibrosis in SSc or bronchial hyper-responsiveness in pSS. Alveolar macrophage activation may contribute to the development of lung fibrosis in SSc.